Rock-Logging-Seismic Integrated Carbonate Reservoir Prediction and Inversion of Mala Oil Field, South Sudan - Deng Daniel Agwang (European Scientific Journal, ESJ, 2026)
Carbonate reservoirs are globally known to exhibit commercial hydrocarbon reserves and probable underground storage for carbon dioxide and hydrogen; conversely, uncertainty and error analysis are often overlooked in quantitative log interpretation and the estimation of petrophysical parameters due to the complexity and heterogeneity of subsurface formations. Traditional methods often fall short in addressing such structural intricacy, making it challenging to accurately predict the properties of carbonate reservoirs and infer their potential, as this study aims to predict carbonate reservoir properties using existing petrophysical and reservoir modelling data, which were simulated to generate various cross-plots for interpretation. The analysed cross-plots (Figures 3, 4, 5, 6, 8, and 9) indicate the presence of a dolomitized limestone reef carbonate reservoir. In contrast, the illustrations (Figures 3, 5, 7, and 8) highlight coral and algae, chalky, mudstone sediments characterised as kerogen-rich hydrocarbon, dominantly oil-gas prone, filled with brine (Figures 5, 6, 8, 10, 11, 12, 13, and 14). These are dominated by moldic, vuggy, or karstic porosity. The selected reservoirs of Mala oil field exhibit good characteristics: moldic-vuggy to karstic porosity and partially weathered, dolomitized limestone lithofacies, indicative of reef-associated carbonate systems. These properties not only support their classification as high-quality (Figure 7) reefal carbonate reservoirs but also suggest their suitability for future carbon dioxide (CO₂) and hydrogen underground storage due to their adequate pore space and potential for long-term seal suppression.